Hypofractionated radiation treatment in the management of breast cancer - Gupta, Apar (Expert Rev Anticancer Ther, 2018)
INTRODUCTION: The standard treatment for early-stage breast cancer is breast conservation therapy, consisting of breast conserving surgery followed by adjuvant radiation treatment (RT). Conventionally-fractionated whole breast irradiation (CF-WBI) has been the standard RT regimen, but recently shorter courses of hypofractionated whole breast irradiation (HF-WBI) have been advocated for patient convenience and reduction in healthcare costs and resources. AREAS COVERED: This review covers the major randomized European and Canadian trials comparing HF-WBI to CF-WBI with long-term follow-up, as well as additional recently closed randomized trials that further seek to define the applicability of HF-WBI in clinical practice. Randomized data is summarized in terms of clinical utility and for a variety of clinical applications. Recently published consensus guidelines and practical implementation of HF-WBI including its broader effect on the healthcare system are reviewed. Finally, an assessment of the emerging evidence in support of hypofractionation for locally advanced disease is presented. EXPERT COMMENTARY: HF-WBI has replaced CF-WBI as the accepted standard of care in most women with early-stage breast cancer who do not require regional nodal irradiation. Early data supports the continued study of hypofractionation in the locally advanced setting, however broad adoption awaits longer follow-up and additional data from ongoing clinical trials.